The Boundaries of Criminal Liability of Cooperative Management and Cooperatives as Corporations in Corruption Crimes - M. Irwan Susanto; Hendro Widodo; Zainal Arifin Hoesein (International Journal of Sociology and Law, 2026)
The increasing incidence of corruption in the cooperative sector demonstrates that cooperatives are not only vehicles for community economic empowerment but may also be used to facilitate abuses of authority that cause state financial losses. This situation raises legal uncertainty regarding the division of criminal liability between cooperative management as individual offenders and cooperatives as corporate entities. This study aims to analyze the regulation of criminal liability for both legal subjects, identify the limits of their respective responsibilities, and formulate legal parameters for determining criminal accountability in corruption cases. The research employs a normative juridical method using statutory, conceptual, case, and comparative approaches through the analysis of legislation, court decisions, and legal doctrines. The findings reveal that existing regulations do not clearly distinguish the criminal liability of cooperative management and cooperatives as corporations. Management is held liable when corruption involves abuse of authority, intent, or personal benefit, whereas cooperatives may be held liable if the offense results from organizational policies, benefits the corporation, or reflects failures in internal supervision. Clearer legal parameters are essential to strengthen legal certainty and promote more effective, proportional, and equitable law enforcement in combating corruption within the cooperative sector.